Subjective wellbeing and body image in college students in Arequipa - Prieto Vela, Andrea (2015)
This study explored the correlation between subjective wellbeing and body image of female students at a university in Arequipa. The sample consisted by 155 female students between 17 and 24 years old from the three professional careers. The participants were evaluated in their respective classrooms. The validation of the Body Shape Questionnaire (BSQ) was calculated using Cronbach’s alpha and obtained a value of 0.92. The results indicated that there is significant negative correlation between the subjective wellbeing and body image (r = -0.478; p < 0.001). It was also noted that there is no statistical significant difference between management and law careers with respect to the subjective wellbeing (t = 0.201; p > 0.05) and body image (t = -0.606; p > 0.05). This shows that the distortion of body image has a negative impact on the subjective wellbeing of women university students.